2005
DOI: 10.1002/mop.20801
|View full text |Cite
|
Sign up to set email alerts
|

Tunable fiber laser based on an etched fiber Bragg grating

Abstract: tively, and can satisfy the typical bandwidth requirement for dualband WLAN applications.The measured radiation patterns for the proposed antenna at 2.45 and 5.25 GHz are shown in Figures 3 and 4, respectively. It can be seen that the radiation patterns at both frequencies have monopolelike radiation patterns. However, in the azimuthal plane ( x-y plane), the radiation patterns at 2.45 and 5.25 GHz are more similar to omnidirectional radiation. The measurements at the other operating frequencies have similar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The etching process was stopped by removing the fibre from the HF bath and immediately submerging it into a saturated aqueous solution of calcium hydroxide for 10 min. Previous investigators have shown that Bragg grating optical performance is not compromised by acid etching [27,28] to diameter as small as 25 μm [29]. However, it has also been shown that fibre optic cables stripped of their polyimide coating suffer from reduced failure and fatigue strength [11].…”
Section: Chemical Etchingmentioning
confidence: 99%
“…The etching process was stopped by removing the fibre from the HF bath and immediately submerging it into a saturated aqueous solution of calcium hydroxide for 10 min. Previous investigators have shown that Bragg grating optical performance is not compromised by acid etching [27,28] to diameter as small as 25 μm [29]. However, it has also been shown that fibre optic cables stripped of their polyimide coating suffer from reduced failure and fatigue strength [11].…”
Section: Chemical Etchingmentioning
confidence: 99%